Alcoholism and Inflammatory Response: Implications for Liver and Cardiovascular Disease - Christian Gabriel Acosta Ricachi; Sheila Ivette Quinapanta Serrano; Álvaro Paúl Moina Veloz (Revista Finlay, 2024)
Alcohol is one of the main drugs consumed in the history of mankind. Prevention of irresponsible alcohol consumption is currently a priority in the health sector. This research aimed to analyze the inflammatory factors that contribute to the development of liver and cardiovascular diseases related to alcoholism. A search was carried out of the scientific literature published between 2019 and 2023 in the PubMed, ScIELO, Scopus and Medline databases. Alcohol can cause damage to various tissues and organs. Among the main mechanisms that cause these injuries are: alterations in the immune response, increased oxidative stress and methylation alterations. Among the multiple conditions it can cause are: cardiovascular disease, stroke, cancer, diabetes mellitus, fetal alcohol syndrome, liver and immune system disorders. A synthesis based on scientific evidence was carried out, which will provide medical professionals with updated knowledge on the pathological and physiological consequences of long-term alcohol consumption.